Education and social education - Rizaeva Husniya Ubaevna (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, opinions are given about the types of education and social education, their place in society. Information about the importance and necessity of education, the scientific traces of the scholars of the East in this matter are presented.